Empowerment and Protection of The Elderly in Islamic Boarding Schools From A Social Fiqh Perspective - yuliatin, yuliatin; Mubarak, Haris; Harun, Hermanto; Effendi, Ghina Nabilah; Adawiyah, Robi'atul (al-'adalah, 2023)
This study aims to describe the pattern of care and protection of the elderly at the Pesantren (Islamic Boarding School) of Syekh Maulana Qori Merangin Jambi. The aim is to study the pattern and mechanism of care as an empowerment effort while examining certain aspects through the perspective of social fiqh which is sourced from the opinions of scholars. This study is a quantitative study using the Nvivo R1.7 data analysis method. The results of this study indicate that among several factors that cause the elderly to be in Islamic boarding schools is because of the wishes of the family or their wishes to avoid family conflict. This study found the fact that while being cared for in Islamic boarding schools, the elderly get peace, comfort, protection, and increased religiosity. This phenomenon also proves that caring for the elderly in Islamic boarding schools does not cause any harm to them at all, in fact, on the contrary, they get many useful benefits according to their conditions and fulfillment of their psychological needs. By using social fiqh,caring for the elderly in Islamic boarding schools can be seen as a highly recommended matter.